POLA MAKAN DAN ASUPAN NATRIUM PADA LANSIA HIPERTENI DI WILAYAH KERJA PUSKESMAS TARERAN - Daniel Robert; Irza N. Ranti; Stefani C. Karundeng (POLTEKKES KEMENKES MANADO, 2015)
Hypertension or high blood pressure is one health problem that is dominant and needs tobe addressed, because the prevalence rate is high and also due to long-term damagecaused has certain consequences. Hypertension often has no signs or symptoms, or oftencalled the